The Opposite Orientation of Product Marketing and Finance Tool Marketing - V. A. Galanov; A. V. Galanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
Product marketing orientates to the increasing appeal of customer goods, while finance tool market – to rising appeal of private saving investment. The authors show that these two forms of marketing hide competition between the growth in consumption and the growth in investment in today’s economy. The growth in consumption reduces relatively the resources of economy for GDP growth, while the growth in investment cut resources providing the rise in population living standard. Ways and methods of marketing available on market do not necessarily promote shaping of reasonable structure and volumes of consumption. No marketing methods of raising finance investment can compete with appeal of private consumption, because of the essence of consumption itself and because of relatively low volume of private savings of the Russian population. This situation, according to the authors, forms an economic basis of maintaining rather low rates of GDP growth in the future.